Pembinaan Generasi Islami melalui Murajaah Surat Pendek dan Shalat Dhuha dalam Pesantren Kilat di Desa Rancalabuh, Kabupaten Tangerang: Developing an Islamic Generation Through Short Qur'an Murajaah and Dhuha Prayer Habituation in a Pesantren Kilat Program in Rancalabuh Village, Tangerang Regency - Mohamad Mualim; Muhammad Zainudin; Mucholik Amin Rizki; Jaka Ghianovan (Khadimul Mujtama’: Journal of Community Service, 2026)
This community service activity was carried out to address the need for religious guidance among children in Rancalabuh Village, Tangerang Regency, who still require stronger support in reading, memorizing, and consistently practicing daily worship. The purpose of the program was to foster an Islamic generation through the murojaah of short Qur’anic chapters and the habituation of Dhuha prayer within a pesantren kilat program. The implementation method used a structured, participatory, and repetitive habituation approach consisting of preparation, implementation, mentoring, and evaluation stages. The participants were elementary school-age children and early adolescents from the Rancalabuh community, supported by parents, community leaders, and local prayer facility administrators. The results showed improvements in participants’ ability to read and memorize short Qur’anic chapters more fluently and confidently, along with better understanding and discipline in performing Dhuha prayer. The program also fostered worship awareness, responsibility, and self-control among the children. Therefore, the pesantren kilat proved effective as a means of Islamic character building that can be sustained through collaboration between families and the community.